Eosinophilic bodies in pyloric and Brunner's gland cells. Issue 12 (December 1992) - Rubio, C A; Hirota, T; Itabashi, M; Jacobsson, B; Lignelid, H
Abstract : A previously unreported cell phenotype occurred in the pyloric and Brunner glands in two gastrectomy specimens. The cells were characterised by homogeneous, eosinophilic material in the cytoplasm. The eosinophilic material had an abnormally strong reactivity for Cystatin C, a protein found recently in the normal secretion of pyloric and Brunner's gland cells. The reason for the apparent cytoplasmic accumulation of cystatin C in the two patients described remains unclear.